Religious Tolerance and Authentic Coexistence in Indonesian Urban Society - Parihat, Parihat (Religió Jurnal Studi Agama-agama, 2024)
This research elucidates religious tolerance in Bandung, as an Indonesian urban context. The research integrates cultural, social, and philosophical insights to uncover the dynamics of tolerance as both a communal practice and an individual ethical commitment. This study employs a qualitative approach, utilizing observation, interviews, and documentation as its primary data collection methods. The key informants for this research are members of the FKUB (Forum Kerukunan Umat Beragama, or Interreligious Harmony Forum), representing the Islamic, Christian, and Confucian traditions. The research employed a descriptive, interpretive, and existential framework to analyze the data and investigate the authenticity and rationality of urban religious tolerance. The study revealed that the Kampung Toleransi (Tolerance Villages) in Bandung were shaped by three key factors: Sundanese cultural roots, urban pluralism, and existential dynamics. From an existentialist perspective, authentic tolerance emerges from conscious and rational choices that transcend societal pressures and conditional acceptance. This phenomenon is consistent with existential principles emphasizing freedom, ethical autonomy, and recognizing life’s resources.